Regional Food and Cuisine: The Case of the Brotos Frutos Culinaria do Cerrado Association in Brazil (Global Journal of Human-Social Science, 2019)
The richness of Brazilian flora and fauna reveal opportunities for agri-food markets, especially regarding the added value of regional foods, brand development, and differentiation strategies. In this context, the aim of the present study was to characterize the business strategies used by the Brotos Frutos Culinária do Cerrado Association, highlighting their strengths and weaknesses. To achieve the proposed objectives, techniques of observation and direct interviews with those responsible for the Association were used. The results revealed the absence of a business plan capable of guiding the organization's practices, a lack of knowledge on the market and on consumer behavior. Suggestions to improve the management are discussed during the study.
Keywords: value creation; entrepreneurship; agribusiness; markets